IMPLEMENTASI PROGRAM KELOMPOK USAHA BERSAMA DI KECAMATAN SINGKAWANG SELATAN - Parameswari E.42009085 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This thesis is intended to determine the process of implementation programme with “Kelompok Usaha Bersama” in the South Singkawang District. This research was conducted based on the problems that occured when programs “Kelompok Usaha Bersama” in the South Singkawang District implemented, with a focus on the implementation of the organization, interpretation and application of the programme. By using the qualitative analysis, the results obtained indicate that the lack of due implementation of the programme “Kelompok Usaha Bersama” in the South Singkawang District on the available guidelines related to the implementation of an organization, interpretation and application. Besides the lack of educational background and training of “Pendamping Kelompok Usaha Bersama” also affect the success implementation of the programme it self, due to lack of knowledge and training that they have an understanding of programme impact on group members; knowledge of “Kelompok Usaha Bersama” will be an understanding of the programme. Keywords: Implementation, Kelompok Usaha Bersama, Pendamping Kelompok Usaha Bersama.